PENGARUH HARGA DAN CITRA MEREK MASKAPAI LION AIR TERHADAP LOYALITAS KONSUMEN DI BANDAR UDARA INTERNASIONAL JENDERAL AHMAD YANI SEMARANG - Yudhakusuma, Alvin; Anne Darasta, You She Melly (Yayasan Education and Social Center, 2025)
This research uses a quantitative approach with a descriptive method. The data were collected through questionnaires distributed to 100 respondents who had used Lion Air services at Jenderal Ahmad Yani International Airport in Semarang. The sampling technique used was purposive sampling, and the data were analyzed using validity and reliability tests, normality test, multikolinearity test, heteroscedasticity test, multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results show that price has a positive and significant effect on customer loyalty, with a significance value of 0.000. Likewise, brand image also has a positive and significant effect with the same significance level. Simultaneously, both variables significantly influence customer loyalty. Among them, price has the most dominant effect, with a regression coefficient value of 4,069. The determination coefficient (R²) of 0.481 indicates that 48,1% of the variation in customer loyalty can be explained by price and brand image, while the remaining 51,9% is influenced by other factors outside this study. Based on these findings, this research aims to provide insight into how price and brand image influence customer loyalty toward Lion Air, as a reference for the airline in formulating strategies to maintain and improve customer satisfaction and loyalty.